2005
DOI: 10.1128/aac.49.5.1679-1687.2005
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial Activity of the Terpene Nerolidol

Abstract: The activity of nerolidol, a sesquiterpene used as a food-flavoring agent and currently under testing as a skin penetration enhancer for the transdermal delivery of therapeutic drugs, was evaluated against Leishmania species. Nerolidol inhibited the growth of Leishmania amazonensis, L. braziliensis, and L. chagasi promastigotes and L. amazonensis amastigotes with in vitro 50% inhibitory concentrations of 85, 74, 75, and 67 M, respectively. The treatment of L. amazonensis-infected macrophages with 100 M nerolid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
1
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(116 citation statements)
references
References 49 publications
3
105
1
7
Order By: Relevance
“…Likewise, researches have attributed to the oxygenated sesquiterpenes the activity against different species of Leishmania (Arruda et al, 2005). In A. coriacea, these constituents represent 39.1% of the sesquiterpene compounds found in its oil.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, researches have attributed to the oxygenated sesquiterpenes the activity against different species of Leishmania (Arruda et al, 2005). In A. coriacea, these constituents represent 39.1% of the sesquiterpene compounds found in its oil.…”
Section: Resultsmentioning
confidence: 99%
“…Trans-nerolidol is an important fragrance and flavour (Berger, 2007). Nerolidol also exhibits antiulcer (Klopell et al, 2007), antileishmanial (Arruda et al, 2005) and insect repelling (Di Campli et al, 2012) activities. It is the main component of the essential oil and the biologically active component from fragrant rosewood (Dalbergia odorifera; Jiang Xiang in Chinese) heart wood; D. odorifera essential oil is used in Traditional Chinese Medicine for dispersing blood stasis in organs/tissues, and applied for treating coronary heart disease and angina pectoris (Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…28,29 but there is no scientific report on antileishmanial activity for unfunctionalized sesquiterpenes, and the mechanisms of action remain unclear. Recent studies on cultures of L. amazonensis promastigotes revealed that 30 This encourages an intensive investigation of the mechanisms of action of terpene essential oils. It has been also suggested that the low density of the essential oils and their ready diffusion across cell membranes contribute to enhance targeting intracellular protozoal malaria parasites.…”
Section: Antileishmanial Activitymentioning
confidence: 99%